European Experience in Constitutional and Legal Guarantees of Freedom of the Media - Bezuglya, Anna A.; Gelunenko, Valeriya V.; Novikov, Andrey B.; Radaeva, Svetlana V.; Tulnev, Mikhail A. (Cuestiones Políticas, 2020)
The document presents the results of a comparative legal analysis dedicated to the constitutions of the European states regarding the identification of norms that guarantee the freedom of the social media in them. Methodologically The study was built on the basis of a dialectical approach to the dissemination of legal phenomena and processes using general scientific methods (systemic, logical, analysis and synthesis) and particular. By way of conclusion, all the evidence shows that, in the most common version, the constitutional regulation of guarantees is concise and includes only the recognition or guarantee of the freedom of the media together with the prohibition of censorship. In more detailed versions, prohibitive or regulatory rules may indicate specific types of liability, administrative procedures, etc. For federal states, it is typical to pay special attention to press matters within the scope of jurisdiction issues.